Hair tourniquet syndrome leading to nipple autoamputation in an adult female: a case report - Alshurafa, Alaa A.; Alshawwa, Khaled (Frontiers in Surgery, 2025)
This is a unique case of hair thread tourniquet syndrome (HTTS) affecting the nipple of an adult female, leading to spontaneous autoamputation, a phenomenon rarely documented in the literature for this anatomical site. A 52-year-old woman presented with changes in the color and shape of her left nipple over two days, with a piece of hair wrapped around it. Despite hair removal, her symptoms worsened, ultimately resulting in necrosis and autoamputation of the nipple. Unlike most reported cases, which involve early intervention preventing severe ischemic damage, this case highlights the rare progression of HTTS to complete tissue loss. The necrotic portion was easily excised under local anesthesia. Awareness of this condition and prompt intervention are crucial to prevent severe complications in adult HTTS.